Public values regarding an urban mangrove wetland in the United Arab Emirates - Assaf, Hamed; Idwan, Sahar; Jallad, Abdul Halim; Ammari, Madiha Z. J.; Al Chaar, Aktham; Kouja, Mahmoud (Journal of Environmental Engineering and Landscape Management, 2022)
Mangrove wetlands are facing an existential threat from rapid socio-economic development. In this study, public environmental values regarding mangrove wetlands in the Ras Al Khaimah (RAK) city in the United Arab Emirates were assessed, considering gender, age, education, income, length of residency in RAK, knowledge of RAK mangrove and awareness of sustainability. A population sample of 427 respondents were face-to-face interviewed. Results suggest that mangrove value orientations are highly associated with length of residency in RAK and awareness of sustainability at significance levels of 0.003 and 0.005, respectively. Value orientations are less associated with age, knowledge of RAK mangrove and education at significance levels of 0.023, 0.039 and 0.095, respectively, being largely independent of gender and income. The majority of the respondents support the preservation of the mangroves even at the expense of economic development. This indicates the need to draft policies and regulations to safeguard the mangroves.